Coronavirus outbreak from early career psychiatrists' viewpoint: What we have learned so far. Issue 1 (1st June 2021) - de Filippis, Renato; Soler‐Vidal, Joan; Pereira‐Sanchez, Victor; Ojeahere, Margaret Isioma; Morimoto, Kana; Chang, Alice; Schuh Teixeira, Andre Luiz; Spadini, Alex Vicente
Abstract: Purpose: Since the World Health Organization declared the coronavirus outbreak a global pandemic several million cases and more than three million deaths have been already confirmed worldwide due to COVID‐19. Design and Methods: Early Career Psychiatrists from all over the world present an overview of what happened in their own countries and what they have learned so far by this experience in everyday clinical practice. Practice Implication: We tried to take a real time picture of this unexpected situation, drawing useful hints for now and the future.